The integrated evaluation of the macro environment of companies providing transport services - Žvirblis, Algis; Zinkevičiūtė, Virgilija (Transport, 2008)
The article presents the main principles of the integrated evaluation of macro environment components and factors influencing the performance of transport companies as well as providing the validated quantitative evaluation models and results obtained in evaluating the macro environment of Lithuanian companies providing transport services. Since quantitative evaluation is growing in importance, the process of developing the principles and methods of business macro environment quantitative evaluation is becoming relevant from both theoretical and practical perspectives. The created methodology is based on the concept of macro environment as an integrated whole of components, formalization and the principle of three‐stage quantitative evaluation. The methodology suggested involves the quantitative evaluation of primary factors and macro environment components as an integral dimension (expressed in points). On the basis of this principle, an integrated macro environment evaluation parameter is established as its level index. The methodology integrates the identification of significant factors, building scenarios, a primary analysis of factors, expert evaluation, the quantitative evaluation of macro environment components and their whole. The application of the multi‐criteria Simple Additive Weighting (SAW) method is validated. The integrated evaluation of the macro environment of Lithuanian freight transportation companies was conducted. As a result, the level indices of all components as well as the level index of macro environment considered as a whole of components were identified. The latter reflects the extent of deviation from an average level of a favourable macro environment. This is important for developing strategic marketing decisions and expanding a strategic area. First published online: 27 Oct 2010